Proses Mendapatkan Naskah Kuno di Sumatera Barat Untuk Disimpan di Perpustakaan Daerah Provinsi Sumatera Barat - Windi, Melisa Novia; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This study aims to (1) describe the process of getting the manuscript in West Sumatra West Sumatra to be recorded in the West Sumatra Provincial Library. (2) describe how the storage process in the ancient manuscripts stored in West Sumatra West Sumatra Regional Library and (3) describe the constraints faced by the West Sumatra Provincial Library in getting the manuscript in West Sumatra. The method used is descriptive method of techniques, observation and interviews with librarians manuscripts acquired by the library in the form of media over manuscripts, manuscript copies of the parent, bought the manuscript from aliwaris manuscript. Ancient manuscripts stored in the Library of the West Sumatra Provincial form of media over manuscripts, manuscript copies of the parent. Codex manuscript stored in cabinets, display case and display cabinet. Keywords: process; manuscript